Metodologia de avaliaç\~ao de resultados: O caso das intervenç\~oes do PAC Urbanizaç\~ao de Favelas - Renato Balbim; Cleandro Krause; Maria Fernanda Becker; Vicente Correia Lima Neto; Maria Martha Cassiolato; Carla Coelho de Andrade (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– This article has its origins on the development of a research program on the evaluation of slum upgrading interventions and policies at IPEA. The final result is a methodological proposal designed for the evaluation of slum upgrading projects included in Brazil's Programa de Aceleraç\~ao do Crescimento (Program for Acceleration of Growth), or PAC. Principles and guidelines of an evaluation process are analyzed, and a handbook of evaluation is here presented, taking into account the scarcity and difficulties of obtaining data and information on the reality of slums, as well as the usual incompleteness of plans and projects. We aim at offering a set of strategies and techniques that fit the conditions posed by the several slum upgrading projects that are presently being contracted, or will still be contracted, in a nationwide basis, both in the first and in the second phases of PAC. Such methodology derives from the systematization of a previous research, for IPEA has already made a meta-evaluation of completed slum upgrading projects and developed a logical model framework for the evaluation of programs' outputs and outcomes, now adapted for project evaluation. We expect that a collection of evaluated projects will serve as inputs to the Brazilian federal government's efforts to the improvement of slum upgrading programs. The function of evaluation, in this text, is twofold: on the one side, transparency, accountability and control; on the other side, reflection, learning and continuous improvement. Finally, this article includes a guide for the implementation of evaluation processes, containing step-by-step instructions for local evaluation teams.
Keywords: R20; 330; outcome evaluation; slum upgrading; logical model; indicators; Programa de Aceleraç\~ao do Crescimento (PAC)